2018
DOI: 10.1007/s00294-018-0916-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into molecular chaperone regulation of ribonucleotide reductase

Abstract: The molecular chaperones Hsp70 and Hsp90 bind and fold a significant proportion of the proteome. They are responsible for the activity and stability of many disease related proteins including those in cancer. Substantial effort has been devoted to developing a range of chaperone inhibitors for clinical use. Recent studies have identified the oncogenic ribonucleotide reductase (RNR) complex as an interactor of chaperones. While several generations of RNR inhibitor have been developed for use in cancer patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 69 publications
2
30
0
Order By: Relevance
“…These results indicate that RRM2 may be a master driver of the aggressive subtypes PCS1 and luminal B by directly or indirectly regulating the expression of critical genes. Ribonucleotide reductase inhibitors have been developed for cancer treatment (Knighton et al, 2018), and we previously reported the potency of the novel RRM2 inhibitor COH29 in prostate cancer (Mazzu et al, 2019). In this study, we confirmed that inhibiting RRM2 activity by siRNA or small molecule (COH29) specifically targets PCS1 and luminal B genes (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…These results indicate that RRM2 may be a master driver of the aggressive subtypes PCS1 and luminal B by directly or indirectly regulating the expression of critical genes. Ribonucleotide reductase inhibitors have been developed for cancer treatment (Knighton et al, 2018), and we previously reported the potency of the novel RRM2 inhibitor COH29 in prostate cancer (Mazzu et al, 2019). In this study, we confirmed that inhibiting RRM2 activity by siRNA or small molecule (COH29) specifically targets PCS1 and luminal B genes (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The Ssa proteins are activated by a large number of J-protein and NEF co-chaperones; binding selectivity and affinity of these to each Ssa remains undetermined. Large-scale analysis of Hsp70 isoform interactomes by high-resolution mass spectrometry of the type seen in (Truman et al 2012(Truman et al , 2015aKnighton et al 2019) would confirm that even the small amino acid differences present in Hsp70 isoforms can greatly impact co-chaperone and client-binding specificity. The Ssa proteins are highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…This increased potency may be related to the destabilization of clients that are the target of these small molecules. For example, Hsp70 activates many proteins involved in the DNA damage response and DNA repair pathways (DDR), including ATM, APE1, PARP1, XRCC1 29 . Recently, studies from our group have established roles for both Hsp70 and DNAJA1 in stability of the RNR complex 8 , 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%